Methodical Toolkit of Formation of Professional Competence of Future Teachers in the Course of Search and Extracurricular Research Activities - Sushchenko, Larysa (Pedagogical Discourse, 2014)
The article describes the author’s approach of using methodological tools in developing the professional competence of future teachers in the course of search and extracurricular research activities. The attention is accented on the need for building modern higher education on the principles of the organization of research activities with practical and pragmatic orientation. The factors of systemic impact on the effective search and research activities of the future teachers are identified and analyzed. Peculiarities of pedagogical accompaniment of professionally-directed, research work of the future teachers within the experimental program of the reserch are grounded. The approaches to working out step-by-step process of organization of the students’ research activity are cleared out.